Marketing Strategy and Service Quality to Enhance Customer Loyalty in Security Industry - Agustiani, Mulia; Pratiwi, Niken Intan (Jurnal Mirai Management, 2025)
The security industry has become an essential part of modern business operations, where trust and reliability are key elements for maintaining customer relationships. In the era of digital transformation, security service companies are challenged to design effective marketing strategies and deliver excellent service quality to retain customers and strengthen loyalty. This study aims to review and analyze existing literature on the role of marketing strategy and service quality in enhancing customer loyalty within the security industry. Using a qualitative approach through literature review, this research examines studies published between 2020 and 2024. The findings indicate that marketing strategies supported by digital transformation, relationship marketing, and service excellence significantly influence customer loyalty. In addition, consistent communication, professionalism, and technology-based service innovation strengthen clients’ trust and create long-term partnerships. Keywords: marketing strategy, service quality, customer loyalty, security industry, digital marketing